Emissivity: A Program for Atomic Transition Calculations (Communications in Computational Physics, 2010)
In this article we report the release of a new program for calculating emissivityand other physical parameters in atomic transition processes. The program, whichcan be downloaded with its documentation and a sample of input and output filesfrom www.scienceware.net/id1.html, passed various rigorous tests and was usedalongside R-matrix and Autostructure codes to generate theoretical data and analyzeobservational data. It is particularly useful for investigating atomic transition lines inastronomical context as the program is capable of generating a huge amount of theoreticaldata and comparing it to observational line list. A number of atomic transitionalgorithms and analytical techniques are implemented within the program and can bevery useful in various situations. The program can be described as fast and efficient.Moreover, it requires modest computational resources.